Estudo químico e farmacológico de folhas da espécie de café Coffea arabica: isolamento de compostos bioativos e avaliação do potencial antioxidante, de inibição da enzima de conversão da angiotensina e de atividade anticolinesterásica - Almeida, Ricardo Farias de (2017)
The present work investigated the presence of mangiferin, chlorogenic acids and unpublished phenolic compounds in Coffea arabica leaves from several regions of Brazil (Ceará, Minas Gerais and São Paulo) and Costa Rica (Heredia and Turrialba), as well in a commercial source. In addition, antihypertensive, antioxidant and anticholinesterase activity of the methanolic extracts and pure substances were evaluated. The chemical study of the methanolic extracts of Coffea arabica leaves using the High-performance liquid chromatography coupled to diode array detector and mass spectrometry using the electrospray ionization interface technique allowed the identification and quantification of 16 substances belonging to the classes of xanthones, chlorogenic acids and flavonoids, along caffeine: neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid, 3,4-dicaffeoylquinic acid, 3,5- dicaffeoylquinic acid, 4,5- dicaffeoylquinic acid, mangiferin, isomangiferin, quercetin-3-Oglucoside, kaempferol-3-O-ramnoglucoside, kaempferol-3-O-diglucoside ramnoside, rutin, rutin glucoside, quercetin-3-O-diglucoside e quercetin-3- O-ramnogalactoside. The last five described substances have never been previously reported in the literature in the genus Coffea. The flavonoids rutin, glucoside rutin, quercetin-3-O-glucoside and quercetin-3-Odiglucoside were isolated by semi-preparative liquid chromatography and had their structures confirmed using the Nuclear Magnetic Resonance technique. About to the quantification of secondary metabolites in Coffea arabica leaves, the samples presented high concentrations of polyphenolic compounds, especially the samples collected in São Paulo, with levels of chlorogenic acid, mangiferine and rutin varying between 1.52-22.45 g / kg, 1.02-10.31 g / kg and 0.27-8.11 g / kg, respectively. The quantification of compounds in Coffea arabica leaves allowed to verify that the production of secondary metabolites in leaves is influenced by several factors, such as sun exposure, mechanical factors, soil fertilization, altitude and leaf age. The release of total mangiferins (mangiferin and isomangiferin) from the infusion of coffee leaf powder was strongly dependent on temperature. The methanolic extracts of Coffea arabica leaves collected in Ceará, Minas Gerais, São Paulo and Costa Rica as well as mangiferin and chlorogenic acid showed antioxidant activity in the DPPH, FRAP, ORAC and HX/XO assays. The three classes of polyphenols all showed excellent correlations in the antioxidant assays. None methanolic extract or pure substance tested showed significant inhibition of the angiotensin-converting enzyme, as no sample showed anticholinesterase activity. The present study show that coffee leaf tea could be an excellent functional beverage, containing many polyphenolic compounds with many positive biological effects, such as high antioxidant activity that may potentially help protect the body against damage linked to oxidative stress, among other types of damage.